The Tpv2 family of retrotransposons of Phaseolus vulgaris: Structure, integration characteristics, and use of genotype classification - Garber, K; Bilic, I; Pusch, O; Tohme, Joseph M.; Bachmair, A; Schweizer, D.; Jantsch, V (Springer, 1999)
The Tpv2 family of transposable elements of common bean, Phaseolus vulgaris, belongs to the Ty1/copia group of long terminal repeat (LTR) containing retrotransposons. By reverse transcriptase (RT)-PCR and by analysis of genomic clones, we characterized four of the approximately 40 copies present in the Phaseolus genome, and the genomic environment of their integration sites. Tpv2 integrated preferentially into actively transcribed regions. While none of the isolated elements had all the functional domains necessary for transposition, analysis of bean cultivars suggested that some members of the Tpv2 family transposed in recent breeding history. Probes derived from Tpv2, as well as flanking genomic sequences, may be useful for classifying Phaseolus cultivars.